Jakość instytucji w gospodarce a efektywność polityki ekonomicznej - analiza porównawcza - Miłaszewicz, Danuta (The Quality of Institutions in the Economy Versus the Efficiency of Economic Policy-Comparative Analysis, 2009)
On the one hand, institutional framework in an economy exerts an impact on the economic policy, but on the other - the results of economic policy affect and shape the character of various institutions. There are numerous relationships between institutions and economic policy, both complementary and substitutional in nature. This study makes an attempt to define the relationship between the quality of institutions in the economy and the efficiency of economic policy. The proceeding has been evaluated with the Worldwide Governance Indicator (WGI), an aggregate measure reflecting the quality of institutions, whereas the latter - with the Global Competitiveness Index (GCI) developed by the World Economic Forum. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 742-749